Strengthening the Community Economy through Empowerment Housewife in Lako Akelamo Village, West Halmahera Regency - Prince Charles Heston Runtunuwu1; Amran Husen (Edujavare Publishing, 2023)
Fish is the biggest asset in Lako Akelamo Village, West Halmahera Regency. Since Lako Akelamo Village was formed, most villagers have worked as fishermen due to the abundance of fish resources in Lako Akelamo Village. This is proven through an interview with the Department of Food Security, Agriculture, and Fisheries Unit 1, which stated that in the past two years, more precisely in 2019-2022, Sahu was one of the contributors to the largest fish catch in North Maluku for two consecutive years. This service activity aims to empower homemakers through targeted counseling, education, and skills training, encouraging their active participation in income-generating activities. The assistance employs participatory rural appraisal (PRA) by engaging the community in extension and education, training and guidance, field assistance, community involvement, research and Monitoring, and partnership development. The result of the study exemplifies the potential of community-led and participatory approaches in enhancing the economic fabric of a village through the empowerment of housewives. The lessons learned from this project can serve as a valuable guide for future development initiatives, emphasizing the importance of collaboration, active engagement, and tailored strategies to achieve sustained economic growth and community well-being.